Strategy and Structure in the Multiproduct Firm - Hill, Charles W. L.; Hoskisson, Robert E. (Academy of Management Review, 1987)
This paper focuses on three strategies for realizing economic benefits from the multiproduct firm: vertical integration, related diversification, and unrelated diversification. The paper identifies economic benefits of the strategies and links them with the organizational control requirements necessary to realize these benefits. Organizational and environmental constraints that can inhibit the realization of these benefits also are considered.